Estimation of human leptin concentration in the subcutaneous adipose and skeletal muscle tissues. (9th March 2015) - Sendlhofer, Gerald; Brunner, Gernot; Schaupp, Lukas; Wutte, Andrea; Ellmerer, Martin; Pieber, Thomas R
Abstract Background Interstitial leptin concentrations in subcutaneous adipose and skeletal muscle tissues were determined by open‐flow microperfusion. Method In 12 lean male subjects (age: 25·6 ± 1·1 years), a zero flow rate experiment using different flow rates was applied. Recovery was determined by urea as an internal reference. In the no‐net‐flux experiments, catheters were perfused with five solutions containing different concentrations of leptin. Concentrations of interstitial leptin were calculated by applying linear regression analysis to perfusate as opposed to sampled leptin concentrations. Results The zero flow rate protocol showed significantly higher concentrations of leptin in the interstitial fluid of subcutaneous adipose compared to skeletal muscle tissue [36·8 ± 10·32 vs. 7·1 ± 2·5% of the corresponding plasma level (P = 0·018)]. The recovery of urea in the samples was comparable for all catheters [79·4 ± 6·8 vs. 83·0 ± 5·8 of the corresponding plasma level, flow rate of 0·3 μL/min; (P = ns)] and was higher when compared to leptin. In the no‐net‐flux protocol, the concentration of leptin in subcutaneous adipose tissue was almost identical to plasma [90. 5 ± 7·0%] and the skeletal muscle tissue concentration of leptin was 23·7 ± 2·5% of the corresponding plasma level. Conclusion Open‐flow microperfusion enables the estimation of leptin concentrations in subcutaneous adipose and skeletal muscle tissues in humans in vivo. This is the first documentation on the use of open‐flow microperfusion to demonstrate that relevant amounts of leptin are also found in skeletal muscle tissue.